SUSTAINABLE AI-POWERED WASTE MANAGEMENT: IMPROVING HEALTH AND SAFETY OUTCOMES FOR WASTE PICKERS IN JAMSHEDPUR CITY THROUGH INNOVATIVE TECHNOLOGICAL SOLUTIONS (CAHIERS MAGELLANES-NS, 2024)
Waste pickers play a vital role in any Indian city's urban waste management system. However, these workers typically face substantial health risks as a result of their exposure to hazardous chemicals and bad working conditions. This empirical study looks at how waste pickers in Jamshedpur City could have better health and safety outcomes through sustainable waste management systems driven by AI. This study attempts to enhance waste management's effectiveness and safety by integrating cutting-edge technological solutions with traditional approaches. Three primary uses of artificial intelligence (AI) are now being investigation: garbage collection; real-time monitoring of hazardous waste sites; and waste transportation and route tracking. The amount of time waste pickers spends collecting waste is reduced when artificial intelligence (AI) tools are used in the waste management process. Intelligent sorting systems lessen the risks that manual sorting poses to human health by automating the separation of recyclable items. For the waste management process to function more smoothly and efficiently, real-time monitoring of garbage collection is also beneficial. The goal of this study was to determine how waste pickers who collect waste from Jamshedpur's towns improve their health as a result of using artificial intelligence (AI). In addition, this study seeks to determine how garbage pickers, who all labour in hazardous conditions and demanding environments, might reduce their risk of illness by using artificial intelligence. To examine the impact of waste pickers' usage of AI technologies in waste management, primary data has been gathered from 117 respondents from Jamshedpur. The impact of AI technologies on waste pickers' health is being examined by the authors using an exploratory and descriptive methodology. The findings of this study will provide valuable insights to waste pickers, govt. and policy makers in designing appropriate strategies to enhance overall health of waster pickers in the society.